TERRA Expression Levels Do Not Correlate with Telomere Length and Radiation Sensitivity in Human Cancer Cell Lines - Smirnova, Alexandra; Gamba, Riccardo; Khoriauli, Lela; Vitelli, Valerio; Nergadze, Solomon G.; Giulotto, Elena (Frontiers in Oncology, 2013)
Mammalian telomeres are transcribed into long non-coding telomeric RNA molecules (TERRA) that seem to play a role in the maintenance of telomere stability. In human cells, CpG island promoters drive TERRA transcription and are regulated by methylation. It was suggested that the amount of TERRA may be related to telomere length. To test this hypothesis we measured telomere length and TERRA levels in single clones isolated from five human cell lines: HeLa (cervical carcinoma), BRC-230 (breast cancer), AKG and GK2 (gastric cancers) and GM847 (SV40 immortalized skin fibroblasts). We observed great clonal heterogeneity both in TRF (Terminal Restriction Fragment) length and in TERRA levels. However, these two parameters did not correlate with each other. Moreover, cell survival to γ-rays did not show a significant variation among the clones, suggesting that, in this cellular system, the intra-population variability in telomere length and TERRA levels does not influence sensitivity to ionizing radiation. This conclusion was supported by the observation that in a cell line in which telomeres were greatly elongated by the ectopic expression of telomerase, TERRA expression levels and radiation sensitivity were similar to the parental HeLa cell line.